Distributive effects of pytoplankton and sea surface temperature on cholera epidemics using satellite remote sensing and geographical information system / Abdul Rauf Abdul Rasam - Abdul Rasam, Abdul Rauf (2011)
Cholera is a diarrhoeal disease caused by Vibrio cholerae (Vc), which occurs naturally in coastal phytoplankton (Chl-a) related with sea surface temperature (SST), shellfish and man. However, there are contradictory of previous findings and local perspective regarding the spatio-temporal effect of Chl-a and SST on cholera epidemics. This study is to investigate the distributive effects of Chl-a and SST variables on the epidemics in the district of Tawau using geographical information system (GIS), satellite remote sensing and epidemiological techniques. The techniques are integrated to analyze the effects qualitatively and quantitively. GIS and Excel statistics were used to examine the spatio-temporal pattern of cholera distribution in the district. ArcGIS spatial statistics, Pearson's correlation coefficient, scatter diagram, MODIS remote sensing image, SST data, and cohort study were used to determine the effect of these environmental variables on the epidemics. Evaluation process was conducted using clinical analysis and public health practice which involved selected health authorities from State Health Department (JKN) Sabah, Institute for Medical Research (IMR) Malaysia, and Ministry of Health, Malaysia (MOH). The key findings showed the effect of Chl-a (r=-0.33267) and SST (r=0.09506) distribution on cholera epidemics in the district are only minimum correlation from 2004 to 2008. The disease could outbreak at anywhere and anytime particularly at high population, unhygienic environment, and close to contaminated water supply especially during the hot and the wet season. The results of evaluation process were also consistent founded in this study. The result not only answer the previous contradict findings and local perspectives on the correlation, but also provides an interesting dimension and new interpretation about constructing appropriate spatial frameworks and predictive model of cholera in the district. This study demonstrates that the environmental factors derived from public domain remote sensing data and GIS technologies could be used as a cholera risk indicator, and cholera control plan in Tawau. As this is the first study initiated in Malaysia using the limited scope, several recommendations are made to enhance the analysis used in order to achieve more significant result.